Quantification and Negation in Event Semantics - Lucas Champollion (Baltic International Yearbook of Cognition, Logic and Communication, 2010)
Recently, it has been claimed that event semantics does not go well together with quantification, especially if one rejects syntactic, LF-based approaches to quantifier scope. This paper shows that such fears are unfounded, by presenting a simple, variable-free framework which combines a Neo-Davidsonian event semantics with a type-shifting based account of quantifier scope. The main innovation is that the event variable is bound inside the verbal denotation, rather than at sentence level by existential closure. Quantifiers can then be interpreted in situ. The resulting framework combines the strengths of event semantics and type-shifting accounts of quantifiers and thus does not force the semanticist to posit either a default underlying word order or a syntactic LF-style level. It is therefore well suited for applications to languages where word order is free and quantifier scope is determined by surface order. As an additional benefit, the system leads to a straightforward account of negation, which has also been claimed to be problematic for event-based frameworks.